Eucalyptus oil nanoemulsion-impregnated chitosan film: antibacterial effects against a clinical pathogen, Staphylococcus aureus, in vitro - Sugumar S (Dove Medical Press, 2015)
Saranya Sugumar, Amitava Mukherjee, Natarajan Chandrasekaran Centre for Nanobiotechnology, VIT University, Vellore, India Abstract: Eucalyptus oil (Eucalyptus globulus) nanoemulsion was formulated using low- and high-energy emulsification methods. Development of nanoemulsion was optimized for system parameters such as emulsifier type, emulsifier concentration, and emulsification methods to obtain a lower droplet size with greater stability. The minimized droplet diameter was achieved using the high-energy method of ultrasonication. Tween 80 was more effective in reducing droplet size and emulsion appearance when compared to Tween 20. Stable nanoemulsion was formulated with Tween 80 as a surfactant, and the particle size was found to be 9.4 nm (1:2 v/v). The eucalyptus oil nanoemulsion was impregnated into chitosan (1%) as a biopolymer in varying concentrations. Further, the film was characterized by moisture content, microscopic study, X-ray diffraction, and Fourier transform infrared spectroscopy. Also, the film with and without nanoemulsion was evaluated against Staphylococcus aureus. The nanoemulsion-impregnated chitosan film showed higher antibacterial activity than chitosan film. These results support the inclusion of nanoemulsion-impregnated chitosan film in wound management studies. Keywords: essential oil, emulsion, biopolymer, impregnation, thin film, wound isolate